Service Quality, Employee Personality, Satisfaction, Trust, and Customer Loyalty in Malaysia’s Restaurant Industry - Kok Ban Teoh; Wang YongDuo; Wang QiMei; Wang Yang; Wang YiLing; PRIYA SETH; ANWESHA HAZARIKA; Daisy Mui Hung Kee (AIBPM Publisher, 2026)
Customer loyalty has become increasingly important for sustaining competitiveness and long-term success in the restaurant industry. This study examines the effects of service quality and employee personality on customer satisfaction and customer loyalty, as well as the roles of customer satisfaction and trust in shaping customer loyalty among restaurant customers in Malaysia. A quantitative approach was employed using a structured questionnaire distributed to customers of Haidilao Malaysia. A total of 220 valid responses were collected and analyzed using regression analysis. The results indicate that service quality (b = 0.30, p = 0.001) and employee personality (b = 0.56, p 0.001) have significant positive effects on customer satisfaction. Customer satisfaction also positively influences trust (b = 0.68, p 0.001), while trust significantly affects customer loyalty (b = 0.59, p 0.001). In addition, service quality (b = 0.25, p = 0.014) and employee personality (b = 0.54, p 0.001) directly contribute to customer loyalty. The findings suggest that employee personality plays a more prominent role than service quality in driving customer satisfaction and loyalty. Both operational and interpersonal service factors contribute to customer loyalty through customer satisfaction and trust.